2004
DOI: 10.1103/physrevlett.93.254801
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Generalization of the Landau Criterion as a New Foundation of the Vavilov-Cherenkov Radiation Theory

Abstract: The relativistic generalization of the Landau criterion is obtained for the determination of threshold conversion of medium elementary Bose-condensed excitation into Cherenkov's photon unbremsstrahlung radiation. In contraposition to classic Vavilov-Cherenkov radiation (VCR) theory, the new VCR theory admits the conditions for effective and direct VCR realization even for high-frequency transverse electromagnetic waves in isotropic plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Of interest is also the possibility of establishing a correlation between the scaling law −8/3 observed in the turbulent spectra of the cosmic plasma in the solar wind and magnetosheath (Passot & Sulem 2015;Chefranov & Chefranov 2021) and the similar exponent of the turbulent spectrum of fluctuations in the density of particles of CRs obtained in this work, and also with a similar spectrum of −8/3, characteristic of fluctuations in the intensity of the surface earth electric field (Anisimov et al 2002). It is of interest to further use the obtained exact solutions in the theory of turbulence and in the new theory of Vavilov-Cherenkov radiation (Chefranov 2004(Chefranov , 2012(Chefranov , 2016 to analyze the problems of describing such turbulence and to consider the mechanism of acceleration of CR particles and their origin. In our paper, it is also shown that shock waves can spontaneously form in a medium consisting of CR particles, which, like shock waves arising from the explosion of supernovae, can cause additional particle acceleration.…”
Section: Discussionsupporting
confidence: 78%
“…Of interest is also the possibility of establishing a correlation between the scaling law −8/3 observed in the turbulent spectra of the cosmic plasma in the solar wind and magnetosheath (Passot & Sulem 2015;Chefranov & Chefranov 2021) and the similar exponent of the turbulent spectrum of fluctuations in the density of particles of CRs obtained in this work, and also with a similar spectrum of −8/3, characteristic of fluctuations in the intensity of the surface earth electric field (Anisimov et al 2002). It is of interest to further use the obtained exact solutions in the theory of turbulence and in the new theory of Vavilov-Cherenkov radiation (Chefranov 2004(Chefranov , 2012(Chefranov , 2016 to analyze the problems of describing such turbulence and to consider the mechanism of acceleration of CR particles and their origin. In our paper, it is also shown that shock waves can spontaneously form in a medium consisting of CR particles, which, like shock waves arising from the explosion of supernovae, can cause additional particle acceleration.…”
Section: Discussionsupporting
confidence: 78%
“…The given example of instability broadens the range of physical problems where a similar phenomenon of dissipative instability was studied earlier and led to a new comprehension of the corresponding phenomena basic mechanisms [16,28,29]. Considered is the application of the theory conclusions when the instability region (6.2) derived from condition (1.3) for a shock wave in real gases and fluids is obtained on the basis of the shock adiabat explicit form (6.1).…”
Section: Discussionmentioning
confidence: 92%
“…We established that the Cherenkov-like thermal waves propagate under the self-propulsion. Geometric characteristics of the Cherenkov thermal cone (triangle) are governed by the inter-relation between the velocity of self-propulsion and the velocity of capillary waves. ,,, The effect is observed for the liquid marbles moving with a velocity larger than the threshold value of . Self-propulsion of liquid marbles generates soluto- and thermo-capillary surface flows.…”
Section: Discussionmentioning
confidence: 99%